Correct choice is (b) 6x-2y+log(x-2y+2)^2=c
To explain: \(\frac{dy}{dx} = \frac{3x-6y+7}{x-2y+4} \rightarrow \frac{dy}{dx} = \frac{3(x-2y)+7}{(x-2y)+4}\)…..here coefficient of x and y in the numerator & denominator are proportional hence substituting \(x-2y = t \rightarrow 1 – 2\frac{dy}{dx} = \frac{dt}{dx}\)
\(1- \frac{dt}{dx} = 2\left(\frac{3t+7}{t+4}\right) \rightarrow \frac{dt}{dx} = \frac{t+4-6t-14}{t+4} =\frac{-5(t+2)}{t+4}\)
separating the variables and hence integrating
\( \int \frac{t+4}{t+2} \,dt = \int -5 \,dx \rightarrow \int \left(1 + \frac{2}{t+2}\right) \,dt = -5x + c\)
t + 2 log(t+2) = -5x + c –> x – 2y + 2 log(x-2y+2) + 5x = c
6x-2y+log(x-2y+2)^2 = c is the solution.